Additive manufacturing-by-design for support structures: a critical review - Jinlong Su; Yang Mo; Peijie Shangguan; Chinnapat Panwisawas; Fulin Jiang; Swee Leong Sing (International Journal of Extreme Manufacturing)
Support structure, a critical component in the design for additive manufacturing (DfAM), has been largely overlooked by additive manufacturing (AM) communities. The support structure stabilises overhanging sections, aids in heat dissipation, and reduces the risk of thermal warping, residual stress, and distortion, particularly in the fabrication of complex geometries that challenge traditional manufacturing methods. Despite the importance of support structures in AM, a systematic review covering all aspects of the design, optimisation, and removal of support structures remains lacking. This review provides an overview of various support structure types—contact and non-contact, as well as identical and dissimilar material configurations—and outlines optimisation methods, including geometric, topology, simulation-driven, data-driven, and multi-objective approaches. Additionally, the mechanisms of support removal, such as mechanical milling and chemical dissolution, and innovations like dissolvable supports and sensitised interfaces, are discussed. Future research directions are outlined, emphasising artificial intelligence (AI)-driven intelligent design, multi-material supports, sustainable support materials, support-free AM techniques, and innovative support removal methods, all of which are essential for advancing AM technology. Overall, this review aims to serve as a foundational reference for the design and optimisation of the support structure in AM.